2020
DOI: 10.1080/07357907.2020.1809668
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Spectrum Infections (COVID-19, MERS, SARS) in Cancer Patients: A Systematic Review of the Literature

Abstract: Background: Coronavirus 2019 (COVID-19) has spread rapidly around the world to become a global pandemic. There is limited data on the impact of COVID-19 among patients with cancer. Methods: A systematic review was performed to determine outcomes of adult patients with cancer affected by coronavirus infections, specifically SARS, MERS, and COVID-19. Studies were independently screened by two reviewers and assessed for quality and bias. Outcomes measured included study characteristics, cancer type, phase of care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…COVID‐19 infection anxiety was measured using a scale adapted from the SARS infection anxiety scale developed and validated during the outbreak of SARS (Cheng & Ng, 2006), a disease belonging to the same atypical coronavirus spectrum as COVID‐19 (e.g., Knisely et al., 2020). The scale's items were adapted from the state anxiety scale of the State‐Trait Anxiety Inventory Form X1 (Spielberger et al., 1970) to refer to an epidemic context.…”
Section: Methodsmentioning
confidence: 99%
“…COVID‐19 infection anxiety was measured using a scale adapted from the SARS infection anxiety scale developed and validated during the outbreak of SARS (Cheng & Ng, 2006), a disease belonging to the same atypical coronavirus spectrum as COVID‐19 (e.g., Knisely et al., 2020). The scale's items were adapted from the state anxiety scale of the State‐Trait Anxiety Inventory Form X1 (Spielberger et al., 1970) to refer to an epidemic context.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study that investigated clinical manifestations of COVID-19, reported that cancer patients had a 3.5-fold increase in the risk of morbidity and an increased risk of severe infection compared to non-cancer patients 41 . In addition to this, according to one comprehensive study, authors reported that cancer patients who have encountered severe acute respiratory syndrome virus (SARS or SARS-CoV-1), Middle East Respiratory Syndrome (MERS) virus, and SARS-CoV-2 have a higher risk of severe complications and death 44 . In general, patients with cancer may be much more vulnerable to SARS-CoV-2 infection 45 .…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel coronavirus of the family Coronaviridae, was identified after the outbreak of the COVID-19 pandemic [ 6 ]. Other coronaviruses such as Middle East Respiratory Syndrome-related coronavirus in 2012 and Severe Acute Respiratory Syndrome coronavirus (SARS, also known as SARS-CoV-1) in 2002 have led to massive epidemics across certain continents, and have especially impacted cancer patients [ 7 , 8 ]. Given the increased incidence rate of SARS-CoV-2, it is likely to co-exist with humans for a long time, like influenza.…”
Section: Introductionmentioning
confidence: 99%